2021
DOI: 10.3389/fsurg.2021.693587
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Case Series of Rare High-Type Anorectal Malformations With Perineal Fistula: Beware of Urethral Involvement

Abstract: Anorectal malformations (ARMs) are one of the more common congenital anomalies encountered in pediatric surgery where the majority are diagnosed in the early neonatal period. The etiology of ARM remains uncertain and is likely to be multifactorial. A majority of ARMs result from abnormal development of the urorectal septum in early fetal life. There can be a broad range of presentation features varying from low anomalies with perineal fistula to high anomalies mandating intricate management. To develop a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…It is more common among Asians. ( 32 – 33 ) While there appears to be a low rate of inheritance in family members, some individuals exhibited autosomal dominant inheritance patterns [ 31 ]. Our subsequent genetic analysis further confirmed that this case represents a typical instance of autosomal dominant inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…It is more common among Asians. ( 32 – 33 ) While there appears to be a low rate of inheritance in family members, some individuals exhibited autosomal dominant inheritance patterns [ 31 ]. Our subsequent genetic analysis further confirmed that this case represents a typical instance of autosomal dominant inheritance.…”
Section: Discussionmentioning
confidence: 99%